PENGELOLAAN BARANG TAMBANG DALAM HUKUM ISLAM DAN HUKUM POSITIF - Siregar, Anwar Habibi (UIN Sunan Kalijaga Yogyakarta, 2014)
Earth minerals are the most important source should get special attention by humans, considering how valuable goods in the the world. In Islamic view, forests and minerals that are unlimited and may not be spent is public property and managed by the state, the results should be given to the people in the form of cheap goods in the form of subsidies for the primary needs of society such as education, health and public facilities. State-who are entitled to handle exploring (including management) minerals and distribute the results to the people of a country, in accordance with Islamic teachings. But also it is possible for states to cooperate with certain circles in realizing production patterns justified and realize justice in the distribution of minerals. In the other side, Mining law stipulates that the government should provide manageability mining rights to the three entities (private enterprises, cooperatives and individuals), and / or all or part of the mining activities which of course after getting a mining license from the government.